PSYCHOLOGICAL ANALYSIS OF PROFESSIONAL ACTIVITY SPECIAL POLICE FORCES - Yarema, Nataliia; Pampura, Igor (PSYCHOLOGICAL JOURNAL, 2018)
The activities of special police forces, associated with the risk to life and characterized by frequent emergencies of extreme situations, is carried out under tense, changing conditions, not regulated by the rigorous schedule of the day, associated with constant wear and possible use of weapons, with the power above other. Different aspects of the problem of professional and functional reliability in the system of law enforcement are dedicated to the work of domestic and foreign scholars, whose works cover only certain issues of psychological peculiarities of the activities of law enforcement officers in extreme conditions. The main psychological characteristics that distinguish the professional activity of the special police forces among other types of professional activity are: the focus on ensuring the legality and observance of human rights; the need to quickly make decisions and have a high responsibility for them; power of attorney; emotional saturation and tension, psychophysical load; the presence of organizational and extreme factors; specificity of objects of professional activity; tolerance to uncertain situations; the importance of effective leadership and team interaction in the divisions. Among the most common psychological constituents of the causes of deaths and injuries of employees of special units during the performance of official duties determine: the miscalculation of planning operational activities; shortcomings in the implementation of intelligence activities; incompleteness of informational and analytical processing of operations; shortage of time when making operational decisions; insufficiently qualified actions of employees during the execution of the planned activities. It should be understood that the perception of the situation as extreme is subjective, which are based on the value-sense, affective areas of the individual and his own experience. In general, extreme situations cause negative changes in the cognitive, emotional, behavioral spheres of the psyche. However, in addition to the negative effects of extreme-psychological factors, they also have a positive effect on the psyche of the police officers, provided that they have a sufficient level of moral and occupational-psychological readiness. Since the activity of special police units is associated with a risk to life, it is carried out under tense and changing conditions, therefore the presence of the formed psychological stability of fighters to stress factors in the conditions of fulfilling professional tasks becomes of paramount importance. To ensure the preservation of life, physical and mental health, as well as the maintenance of a high level of efficiency of professional activities of employees of special police units, allows the system of legal, special, tactical, pedagogical and psychological measures that called personal professional security. It is based on a sufficient level of professional preparedness of fighters, which also includes the possession of safe professional practices, the formation of a personalized survival facility, and psychological qualities that will allow an adequate assessment of the situation, the management of a sense of fear, making quick and correct decisions and not losing self-control in dangerous situations. Consequently, the behavior of an employee in psychologically stressful and extreme situations is determined by his professional competence, motivation and personal psychological readiness, ability to professional security. An important prerequisite for the high reliability of the personnel of special police units is the formation of psychological readiness for fighters to perform professional tasks, the presence of a complex of necessary psychophysiological properties, professional qualities, continuous professional development of employees, and also developed team interaction in the unit. Further research requires the definition of clear criteria for psychological fitness for service in the divisions, as well as the prediction of the success and failure of the professional activities of specially trained police officers.